If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4p-2)=-24
We simplify the equation to the form, which is simple to understand
2(4p-2)=-24
Reorder the terms in parentheses
+(+8p-4)=-24
Remove unnecessary parentheses
+8p-4=-24
We move all terms containing p to the left and all other terms to the right.
+8p=-24+4
We simplify left and right side of the equation.
+8p=-20
We divide both sides of the equation by 8 to get p.
p=-2.5
| (x+4)(x+2)=x-(1-x^2) | | 1/2(6-3)=5/2 | | -k^2+11k-15=3 | | 18.9=2.1 | | (2-b)(2+5)-11=24 | | 7-x-x=-1 | | 27b=59 | | 7x=8+6 | | 4x+5=x-2 | | (a+1)(15-2)+3=42 | | 2x+70-5x=31 | | =(3x^3y^4)(4xy^5) | | 6x^2+17x-12=0 | | 2u-3= | | 3+5x=39+6 | | 23-12(1-9)=12 | | 3=4-1(x+1) | | 80x+8=76 | | 2x+26=9x+4 | | 4*x+30=4.50*x | | (6X-4)(X+3)=2X(3X+4) | | [(5-x)(-5-x)(x)-45]-(5-x)(-9)=0 | | 12x+5=30 | | 2=3(m+4) | | 10x+50=150 | | y=4-4(2) | | y=4-4(1) | | 5-x=-10 | | y=4-4(0) | | y=4-4(-1) | | y=4-4(-2) | | -4+5y= |